РОЛЬ ПРОФЕСІЙНОГО ПОРТФОЛІО У ФАХОВІЙ ПІДГОТОВЦІ ТА СТАНОВЛЕННІ СТУДЕНТІВ - Перхайло, Неля (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті проаналізовано педагогічні засади формування професійної компетентності майбутніх соціальних педагогів з використанням методу професійного портфоліо. Соціально-педагогічна діяльність заснована на різних видах і формах спілкування та вимагає вмінь будувати ефективну символічну комунікацію. Розглянуто педагогічні можливості професійного портфоліо і досвід упровадження технології портфоліо до освітньої діяльності педагогічного ВНЗ. У статті описано різні підходи до визначення поняття «портфоліо», рекомендовано створення і використання портфоліо у процесі фахової підготовки майбутніх соціальних педагогів. Обґрунтовано застосування конкретної технології формування мобільності студента у процесі його професійного становлення і розвитку. Публікація доводить, що підготовка майбутніх соціальних педагогів до фахової діяльності тісно пов’язана з формуванням професійно-комунікативної компетентності, особистісних характеристик, системною підготовкою до ефективного фахового спілкування. Публикация представляет педагогические основы формирования профессиональной компетентности будущих социальных педагогов с использованием метода профессионального портфолио. Рассмотрены его педагогические возможности и опыт внедрения этой технологии в образовательную деятельность педагогического вуза. В статье приводится описание различных подходов к определению понятия «портфолио», рекомендуется создание и использование портфолио в ходе профессиональной подготовки будущих социальных педагогов. Исследования связаны с разработкой конкретной технологии формирования мобильности выпускника в процессе его профессионального становления и развития. Публикация подтверждает, что профессиональное образование будущих социальных педагогов включает в себя необходимость формирования у студентов профессионально-коммуникативной компетентности, личностных характеристик, системную подготовку к эффективной профессиональной самопрезентации. The structure of the competence of the social teacher is considered in the article. The ways of optimization of the process of formation of professional competence in the process of formation of the future specialist are explored. The publication presents the analysis of the problem of professional training of the future social pedagogues at the higher educational establishment. The pedagogical bases of formation of professional competence with the use of method of professional portfolio for future social workers are analyzed in the article. Socio-pedagogical activity based on different types and forms of communication requires skills to build effective communication. Pedagogical possibilities of a professional portfolio and experience of implementing technology of portfolio in the educational activity of pedagogical university are considered. The article describes various approaches to the definition of «portfolio» and recommends the creation and using of portfolios in the process of professional training of future social pedagogues. The research is associated with the development of specific technology of formation mobility of alumnus in the process of his formation and development at the University. The publication proves that the training of the future social teachers to professional activity is closely connected with the formation, particularly professionally-communicative competence, personal characteristics, systematic training to effective professional communication.